2013
DOI: 10.1007/s00520-013-1827-2
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Chinese perspectives on do-not-resuscitate (DNR) orders from an examination of DNR order form completeness for cancer patients

Abstract: PurposeDiscussing end-of-life care with patients is often considered taboo, and signing a do-not-resuscitate (DNR) order is difficult for most patients, especially in Chinese culture. This study investigated distributions and details related to the signing of DNR orders, as well as the completeness of various DNR order forms.MethodsRetrospective chart reviews were performed. We screened all charts from a teaching hospital in Taiwan for patients who died of cancer during the period from January 2010 to December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…Since its foundation, the organization had launched a website, called “Choice and Dignity,” to provide online advice on making living wills [ 30 ]. However, we should be aware that although there is a lot of evidence regarding ACP and end-of-life care discussions in Western countries, cultural attitudes towards such issues are different in Chinese societies [ 31 ]. Currently, there has been insufficient research to demonstrate the benefits of ACP to eastern Asian patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since its foundation, the organization had launched a website, called “Choice and Dignity,” to provide online advice on making living wills [ 30 ]. However, we should be aware that although there is a lot of evidence regarding ACP and end-of-life care discussions in Western countries, cultural attitudes towards such issues are different in Chinese societies [ 31 ]. Currently, there has been insufficient research to demonstrate the benefits of ACP to eastern Asian patients.…”
Section: Discussionmentioning
confidence: 99%
“…EOL care planning is therefore seldom discussed early, and DNR orders are more often signed at the last moment. Under such circumstances, it is understandable that all DNR orders were signed by surrogates instead of the patients themselves [14].…”
Section: Discussionmentioning
confidence: 99%
“…In Chinese culture, almost all DNR orders are signed by surrogates because patients are reluctant to discuss death with medical professionals or family members [14]. In our current retrospective study, we performed an 11-year evaluation to investigate the clinical features of patients with advanced-stage lung cancer who died in hospital and to explore the factors contributing to the signing of DNR orders.…”
Section: Introductionmentioning
confidence: 99%
“…In a multisite registry study in the United States, Perman et al reported that women are more likely than men to establish DNAR. [28] Other studies, including a study that enrolled hospitalized older adults who required a surrogate decision-maker in the United States [16] and a Taiwanese study that enrolled cancer patients, [29] demonstrated no signi cant gender difference. We speculate that there are some paternalistic perspectives in Japan that autonomy is more emphasized among men than women, while women need to be "protected" from serious medical information.…”
Section: Discussionmentioning
confidence: 99%